Predicting the 2023/24 El Niño from a multi-scale and global perspective - Ruikun Hu; Tao Lian; Ting Liu; Jie Wang; Xunshu Song; Hui Chen; Dake Chen (Communications Earth & Environment)
Abstract The 2023/24 El Niño ranks as the second strongest event in the twenty-first century thus far. The event exhibited a two-step warming tendency and two warming centers, which could not be explained by the heat content buildup. Here, by conducting observational analysis and model experiments, we show that the record-breaking pantropical warming in 2023 mitigated this El Niño and confined the warming to the eastern basin, and that a series of westerly wind bursts induced another warming center in the central equatorial Pacific toward the end of 2023. Yet the effects of pantropical forcing and wind bursts coincidentally offset each other, leaving the heat content buildup appearing as the primary cause of the 2023/24 El Niño. Our results not only confirm the essential role of equatorial ocean heat recharge for El Niño development, but also demonstrate the necessity of accounting for multi-scale interactions from a global perspective to predict El Niño.